Oxidation and passivation of the uranium nitride (001) surface. (December 2022) - Lawrence Bright, E.; Darnbrough, J.E.; Goddard, D.T.; Griffiths, I.; Cattelan, M.; Springell, R.
Abstract: The oxidation of uranium mononitride is a potential issue when considering this material as a nuclear fuel. This work investigates the rate and mechanism of this reaction at room temperature, giving insight into fuel surface oxidation during manufacture and storage. Chemical and structural investigation of the ideal surface of an epitaxial ( 0 0 1 ) UN thin film, shows that a UO 2 + x N y layer forms on the surface, highlighting the need for better understanding of the U-N-O system. Below this, a U 2 N 3 interlayer is detected. The topotactic formation of these layers is predicted to play a critical role in the passivation measured during long-duration structural investigation. Graphical abstract: Highlights: UN surface oxidation on a single crystal sample gives insight into oxidation. X-ray reflectivity measurements performed over time show passivation of the surface. Multi-technique analysis shows uranium oxynitride forms in ambient conditions. A U2 N3 interlayer is seen between the surface oxide and UN film.